2018
DOI: 10.1590/1678-7757-2017-0437
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistological study of the effect of vascular Endothelial Growth Factor on the angiogenesis of mature root canals in rat molars

Abstract: Tissue bioengineering has been applied to Endodontics to seek a more biological treatment. The presence of blood vessels is crucial for cell nutrition during tissue formation.ObjectiveThis study analysed the application of vascular endothelial growth factor (VEGF) in the angiogenesis of mature root canals.Material and methodsUpper first molars of twelve 13-week old Wistar male rats were used. The root pulp of the mesiobuccal canal was removed and the root canal instrumented with K-files up to size #25. Periapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Additionally, it is known that angiogenesis is essential for new tissue formation in the process of repair, allowing cells to receive the necessary nutrients for their proliferation and differentiation. 30 Therefore, blood vessel formation has been associated with more advanced tissue repair in experimental models in vivo. 31 Borsatto et al, 4 in a qualitative analysis of apical periodontitis treated with aPDT or calcium hydroxide dressing, demonstrated that calcium hydroxide induced greater proliferation of blood vessels, corroborating with the present study that confirmed this finding quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is known that angiogenesis is essential for new tissue formation in the process of repair, allowing cells to receive the necessary nutrients for their proliferation and differentiation. 30 Therefore, blood vessel formation has been associated with more advanced tissue repair in experimental models in vivo. 31 Borsatto et al, 4 in a qualitative analysis of apical periodontitis treated with aPDT or calcium hydroxide dressing, demonstrated that calcium hydroxide induced greater proliferation of blood vessels, corroborating with the present study that confirmed this finding quantitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding angiogenesis, a logical pulpal response to an irritating agent is hyperemia (54) , leading to increased blood cell count in blood vessels and the connective pulp tissue (55,56) . This is considered a key factor in tissue repair, as it provides essential nutrients for cell proliferation and differentiation (57) . Hence, more advanced tissue repair is often associated with increased blood vessel formation (58) .…”
Section: Discussionmentioning
confidence: 99%
“…However, another study showed vascularization and new bone regeneration after scaffold-mediated VEGF led to similar results as a control group, with only 26% of the defect covered by newly formed bone 12 weeks after injury, suggesting that VEGF-mediated vascularization alone is insufficient to support a robust regenerative response. Previous studies have also demonstrated the ability of VEGF and FGF-2 to promote dental pulp angiogenesis. The delivery of VEGF (together with dental pulp stem cells (DPSCs)) from heparin-conjugated gelatin microspheres in tooth roots also supported formation of vascularized pulp tissue …”
Section: Current Craniofacial Tissue Regenerative Approaches That Tar...mentioning
confidence: 99%